2020
DOI: 10.1088/1361-6641/ab9fab
|View full text |Cite
|
Sign up to set email alerts
|

The impurity size-effect and phonon deformation potentials in wurtzite GaN

Abstract: Doping induced changes in lattice parameters are investigated experimentally for the shallow donors silicon and germanium in thin-film wurtzite a-plane GaN. Silicon doping results in a lattice contraction while germanium doping results in a small but measurable lattice expansion. By high-resolution x-ray diffraction, we are able to determine the isotropically averaged size-effect with high accuracy. The analysis procedure yields en passant results for the phonon deformation potentials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, these equations are more versatile in evaluating the strain along each axis in c-plane GaN. For wurtzite GaN, the phonon deformation potentials a E2 , b E2 , and c E2 are − 850 ± 25 cm −1 , − 920 ± 60 cm −1 , and 65 ± 20 cm −1 , respectively 28,29 . The elastic stiffness constants C 13 and C 33 are 93.4 GPa and 391.0 GPa, respectively 30 .…”
Section: Derivation Of the Raman Frequency-to-strain Conversion Equationmentioning
confidence: 99%
“…Therefore, these equations are more versatile in evaluating the strain along each axis in c-plane GaN. For wurtzite GaN, the phonon deformation potentials a E2 , b E2 , and c E2 are − 850 ± 25 cm −1 , − 920 ± 60 cm −1 , and 65 ± 20 cm −1 , respectively 28,29 . The elastic stiffness constants C 13 and C 33 are 93.4 GPa and 391.0 GPa, respectively 30 .…”
Section: Derivation Of the Raman Frequency-to-strain Conversion Equationmentioning
confidence: 99%
“…In addition, the XRD data could be used to quantify the substitution of Zn using an equation describing the size effect of impurities on the lattice constant: ∆a/a = β size N i (48)(49)(50). Here, a is the lattice constant, Δa is the difference between the lattice constants, β size is the contraction coefficient given as (r i − r h )/ (r h × N h ) (where r i is the tetrahedral covalent radius of the impurity element (that is, Zn), r h is the tetrahedral covalent radius of the host element (that is, In), N h is the concentration of the host atom), and N i is the concentration of the impurity (48)(49)(50). From this relation, it was found that the Zn/In ratio for the p-InAs NCs is 0.17, indicating that 15% of In atoms in the lattice NCs are substituted with Zn.…”
Section: Channelmentioning
confidence: 99%